2001
DOI: 10.1161/01.cir.103.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Local Delivery of Enoxaparin to Decrease Restenosis After Stenting: Results of Initial Multicenter Trial

Abstract: This is the first prospective randomized trial in which the local delivery of a drug, enoxaparin, resulted in significant reduction in late luminal loss and restenosis after stent implantation in de novo coronary lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 41 publications
1
14
0
2
Order By: Relevance
“…One of the primary causes of vein graft failure is vascular smooth muscle cell (VSMC) proliferation. Studies in cell culture and animal models have shown that heparin is capable of inhibiting vascular smooth muscle proliferation, and human clinical trials have suggested that low molecular weight forms of heparin can inhibit intimal hyperplasia associated with vein graft failure (Kiesz et al, 2001;Wilensky et al, 2000). Perhaps an SASTG vector codelivered with heparin may synergistically confer higher levels of gene expression and prevent initial onset of intimal hyperplasia.…”
Section: Clinical Situations In Which Sastg Plus Heparin Would Be Benmentioning
confidence: 99%
“…One of the primary causes of vein graft failure is vascular smooth muscle cell (VSMC) proliferation. Studies in cell culture and animal models have shown that heparin is capable of inhibiting vascular smooth muscle proliferation, and human clinical trials have suggested that low molecular weight forms of heparin can inhibit intimal hyperplasia associated with vein graft failure (Kiesz et al, 2001;Wilensky et al, 2000). Perhaps an SASTG vector codelivered with heparin may synergistically confer higher levels of gene expression and prevent initial onset of intimal hyperplasia.…”
Section: Clinical Situations In Which Sastg Plus Heparin Would Be Benmentioning
confidence: 99%
“…Restenosis has been characterised as a return to ≥70% stenosis and loss of ≥50% of initial gain; the loss of ≥0.7 mm of the vessel diameter; ≥50% stenosis; loss of 50% of initial gain; 50-75% stenosis; % loss of initial gain; change from <50% to ≥50% stenosis; ≥50% stenosis and >50% of initial gain or >20% luminal diameter; or the recurrence of clinical symptoms or adverse events. Binary stenosis divides the cohort of patients (or blockages) into those with <50% stenosis and those with ≥50% stenosis (regardless of initial gain) [5,8,14,21,22,46,53,[73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88]. Vein graft disease is usually measured as % stenosis.…”
Section: What Are Restenosis and Vein Graft Disease?mentioning
confidence: 99%
“…Clinically, systemic high dose LMWHs (with or without pretreatment) may improve patency in peripheral bypass grafts [39], but may not prevent restenosis [74,78,80,81]. Further clinical studies of locally delivered LMWH pinned in place with a stent after drug administration showed a decreased the degree of restenosis [82], but a study on "unsecured" LMWH delivered in a similar manner found that the drug was not effective [164]. It may be that LMWH needs to be held in place in order to act as an antirestenotic agent.…”
Section: Antithrombotic and Antiplateletmentioning
confidence: 99%
See 1 more Smart Citation
“…Hung Su reported on 9 cases of TRAS treated with primary stenting after PTA without any evidence of any recurrence after a 4 year follow-up [13]. A novel development to reduce stent occlusion was the introduction of stents that release agents like rapamycin and enoxaparin locally to inhibit intimal hyperplasia [36].…”
Section: Angioplasty and Stentingmentioning
confidence: 99%